Impact of culture and knowledge acquisition to organizational success: Study on Chinese and Malay small firms - Nik Muhammad, Nik Maheran; Md Isa, Filzah (Canadian Center of Science and Education, 2009)
Research generally concludes that small businesses contribute to economic development.In Malaysia, small firm’s particularly Chinese small firms have played a very important role for economic growth in this country.Chinese firms have managed to survive, grow and succeed either in Malaysia or anywhere else in the world.Most prior research found that the success factor was related to their socio-cultural context.However, previous studies have found the similarities on the cultural values of the Malays and Chinese which derived from ‘Budi Complex’ and ‘Confucianism’ respectively.It was particularly on certain selected values related to self, time and epistemology.Therefore, this paper tries to identify other reasons behind the success factor of the Chinese as compared to the Malay small firms.Thus, looking at the perspective of Knowledge Base View theory, this paper proposed that cultural values are not a mere factor that affect the way Chinese small firms market their operation.The current study thus proposed that how Chinese and Malays acquire and share knowledge, have significant contribution to their success or their failures.